2021
DOI: 10.1016/j.jbc.2021.100831
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation promotes proteasomal degradation of human Rad17 protein through the N-terminal destruction boxes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The K/R359–363A mutant of this construct was deficient in the accumulation in the nucleolus and equally distributed in the nucleolus and the nucleoplasm. This mutation also increased the cytoplasmic localization (42%, Figure 2 A,B and Figure S1A,B ) relative to WT, as was shown recently [ 14 ]. EGFP alone was equally distributed in the nucleolus and the nucleoplasm, and no specific localization in the nucleoplasm or the cytoplasm was observed ( Figure 2 A,B and Figure S1A ).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The K/R359–363A mutant of this construct was deficient in the accumulation in the nucleolus and equally distributed in the nucleolus and the nucleoplasm. This mutation also increased the cytoplasmic localization (42%, Figure 2 A,B and Figure S1A,B ) relative to WT, as was shown recently [ 14 ]. EGFP alone was equally distributed in the nucleolus and the nucleoplasm, and no specific localization in the nucleoplasm or the cytoplasm was observed ( Figure 2 A,B and Figure S1A ).…”
Section: Resultssupporting
confidence: 86%
“…In our recent study, we found that EGFP fused with Rad17 E295–D380 peptide showed exclusive nuclear localization [ 14 ]. In this study, we further characterized the central basic domain of Rad17 spanning N339–D380 ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations